Phytosociological Studies in the Dry Red Sanders (pterocarpus santalinus L. f.) Bearing Forest Areas of Eastern Ghats, Andhra Pradesh - Pattanaik, S.; Rao, N. Rama; Rajesh, K.; Reddy, G. R. S.; Reddy, M. R. G. (Indian Forester, 2014)
An intensive study was conducted to quantitatively assess the composition and structure of vegetation in the dry red sanders (Pterocarpus santalinus L. f.) bearing forest areas of Eastern Ghats, Andhra Pradesh. A total of 243 stems (≥10 cm dbh) belonging to 40 tree species and 21 families were enumerated in 45 quadrats of 100 m2 each, spread over five study sites. Tree communities at the five sites differed in composition, density, dominance and structure. The number of species (species richness) across study sites ranged from 5 to 20. The tree density across study sites ranged from 622.2 stems ha-1 to388.9 stems ha-1 . The basal area across study sites ranged from 15.884 m2 ha-1 to 7.351 m2 ha-1 . The Shannon-Weiner Index (H') of species diversity varied from 2.765 to 1.414. Syzygium alternifolium, Anogeissus latifolia and Chloroxylon swietenia were found to be the predominant species at the study sites. The relative position of red sanders in the community was found to be fifth and beyond.Red sanders was conspicuously absent from the higher diameter classes. The probable cause for this absence and its implications are discussed.